The Effect of Ability in Memorizing Al-Qur'an on The Completeness of Learning - Hasanah, Uswatun; Bunaya; binti Ahmad Sahimi, Mardhiah (Universitas Achmad Yani Banjarmasin, 2024)
: Al-Qur’an is defined as a kitab that contains miracles and it is written in a mushaf whose purity is maintained forever, while learning completeness is a person's mastery of learning outcomes measured by values / numbers. This research wants to find out the effect of ability in memorizing Al-Qur’an on the completeness of learning students in class IV MTA Al-Amien Prenduan. The data collection technique uses questionnaires along with report books with 18 students as respondents. Data analysis using simple linear regression, namely, Ha: there is an effect of ability in memorizing Al-Qur’an on the learning completion of class IV MTA Al-Amien Prenduan. The goal is to find out whether there is a significant effect between independent variables and dependent variables. This research is in the form of quantitative research with a causal type. After calculations were carried out with the Statistical Package For Social Science (SPSS) Program Version 25, a significant value of 0.231 smaller than 0.05 was obtained and based on the t value, it was known that the calculated t value was greater than the table t (2.191 greater than 2.100) for the variable Y. So it can be concluded that the ability in memorizing Al-Qur’an affected the completeness of the Santri Class IV MTA Al-Amien Prenduan